Tata kelola penyelenggaraan pemerintahan Kelurahan tiroang kecamatan Tiroang Kabupaten Pinrang - Firmansyah Firmansyah; Muhammad Rais R; Herman D (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe and analyze the current state of governance in Tiroang Village and to identify and analyze various factors that influence the effectiveness and efficiency of governance at the village level, particularly in Tiroang Village, Tiroang Subdistrict, Pinrang Regency. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. Informants consist of the Village Head, Village Secretary, Administrative Staff, Community Empowerment Institutions, and Community Leaders. Data analysis was performed using the Nvivo application. The results of the study show that government administration in Tiroang Village has basically shown a positive direction with a clear organizational structure between the village head, secretary, and administrative staff, relatively good coordination with the subdistrict, LPM, and the community, as well as the provision of public services oriented towards ease of access. However, the results also show that the effectiveness of governance still faces obstacles, such as a limited number of officials, inadequate infrastructure, and uneven levels of community participation, meaning that residents' aspirations are not fully accommodated in decision-making. This condition reflects that although the principle of good governance has begun to be implemented, its application still requires further strengthening. Meanwhile, the effectiveness and efficiency of governance in Tiroang Village is influenced by coordination with higher levels of government, the level of community participation, the competence and division of tasks among officials, and the availability of infrastructure, including information technology. To improve performance, it is necessary to strengthen coordination, increase community participation, develop the capacity of officials, and maintain and optimize supporting facilities so that public services can be more adaptive, transparent, and responsive.